The Antigenotoxic Activity of Brown Seaweed (Sargassum sp.) Extract Against Total Erythrocyte and Micronuclei of Tilapia Oreochromis niloticus Exposed by Methomyl-Base Pesticide - Kilawati, Yuni; Islamy, R Adharyan (The Journal of Experimental Life Science, 2019)
Pesticides are widely applied in the agriculture sector to protect crops and pest control. The poisonous substance of pesticides will affect all of the organisms, either target and non-target organisms. Fish can play the role of an indicator of genotoxic presence in aquatic environments. Polysaccharide extracts from sargassum have promising anti-genotoxic potential. This study aimed to analyze the anti-genotoxic activity of brown seaweed (Sargassum polycystum) methanol extract against erythrocyte and micronuclei of tilapia exposed by methomyl-base pesticide. Brown seaweed (Sargassum sp.) purchased from farmers in Sumenep Regency, Madura, East Java, then macerated using methanol 1: 3 (w / v) for 3x24 hours at room temperature. The phytochemical screening was including flavonoids, alkaloids, triterpenes, saponins, and tannins. Tilapia fish (TL ± 9-12cm) purchased from the Technical Application Unit of Freshwater Fish (UPT Perikanan Air Tawar), Sumberpasir, Malang, East Java. The result of this study showed that exposure of methomyl-based pesticides in the concentration of 4.015 ppm indicates the formation of micronuclei of 318.33 ‰. The increased concentration of extract treatment is directly proportional to the decrease of micronuclei. It means that sargassum extract can reduce the genotoxic effect on exposed tilapia by methomyl-based pesticides. The best concentration of Sargassum sp. extract that can reduce genotoxic was D (200 ppm). Keywords: Antigenotoxic, Extract, Methomyl, Pesticides, Sargassum sp., Tilapia.